2018
DOI: 10.1029/2018wr023165
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Geophysical Inversion Uncertainty Using Airborne Frequency Domain Electromagnetic Data—Applied at the Province of Zeeland, the Netherlands

Abstract: An accurate understanding of the fresh‐saline distribution of groundwater is necessary for effective groundwater management. Airborne electromagnetic (AEM) surveys offer a rapid and cost‐effective method with which to map this, offering valuable additional information about the subsurface. To convert AEM data into electric conductivity and ultimately groundwater salinity, an inversion is undertaken. A number of algorithms are available for this purpose; however, these are affected by significant uncertainty, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 65 publications
(170 reference statements)
1
22
0
Order By: Relevance
“…Instead, we analyse resistivity–depth functions derived from already existing smooth inversion models because we do not focus on optimizing the inversion as discussed by King et al . ().…”
Section: Automatic Detection Of Fresh–saline Groundwater Interfacesmentioning
confidence: 97%
“…Instead, we analyse resistivity–depth functions derived from already existing smooth inversion models because we do not focus on optimizing the inversion as discussed by King et al . ().…”
Section: Automatic Detection Of Fresh–saline Groundwater Interfacesmentioning
confidence: 97%
“…Such a solution is always a simplified image of the subsurface. Comparison studies (e.g., Delsman et al 2018 andKing et al 2018), however, demonstrated that the majority of models were able to reveal the principle layered resistivity features. A further challenge occurs if the subsurface is strongly heterogeneous in the lateral direction.…”
Section: Hem Data and Inversionmentioning
confidence: 99%
“…Furthermore, resistivity structure is estimated from AEM data through inverse modeling, leading to uncertainty in how well resistivity itself is known. This is a particular concern for the narrow range of resistivity values pertinent to mapping saline and brackish groundwater, and different deterministic inversion algorithms have been shown to have measurable impacts on salinity mapping outcomes (King et al, 2018). The approach presented in this paper uses a Bayesian inversion (Minsley, 2011) to develop statistical models of resistivity derived from AEM data and local correlations between resistivity and salinity to quantify the joint uncertainty in both the interpretational relationship and in how well resistivity is known, following recent work by Christensen et al (2017) using synthetic AEM data to predict lithologic classes.…”
Section: Salinity Mapping Using Aem Datamentioning
confidence: 99%